2016
DOI: 10.21077/ijf.2016.63.4.59010-25
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of methicillin resistant Staphylococcus aureus in selected seafood markets and aquaculture farms in Kerala, south-west coast of India

Abstract: A study was carried out to understand the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) in selected seafood commodities, market environment as well as in aquaculture farms in Kerala, along the south-west coast of India. Two hundred and thirty three samples comprising finfish, crustaceans, molluscs and fishery environmental samples from markets as well as aquaculture farms were collected and screened for the presence of MRSA. The S. aureus isolates obtained from the samples were checked for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…These results are in contrast to a previous and first report of MRSA in cage‐cultured healthy tilapia (Atyah et al, ), with a relatively lower prevalence of S. aureus but a higher percentage occurrence of MRSA. Murugadas, Toms, Reshmi, and Lalitha () also reported MRSA in some aquaculture settings. Although uncommon as a cause of fish disease, MRSA was recently implicated in a disease outbreak in aquaculture in Egypt (Soliman et al, ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These results are in contrast to a previous and first report of MRSA in cage‐cultured healthy tilapia (Atyah et al, ), with a relatively lower prevalence of S. aureus but a higher percentage occurrence of MRSA. Murugadas, Toms, Reshmi, and Lalitha () also reported MRSA in some aquaculture settings. Although uncommon as a cause of fish disease, MRSA was recently implicated in a disease outbreak in aquaculture in Egypt (Soliman et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…Several other studies have reported the prevalence of MRSA in humans, animals, and other livestock (Ali et al, ; Basanisi et al, ; Ge et al, ; Otter & French, ; Strommenger et al, ). However, the prevalence of MRSA in retail, frozen, processed fish, and other seafood (Kumar, Kasim, Lekshmi, Nayak, & Kumar, ; Murugadas et al, ; Siiriken, Yildirim, Güney, Erol, & Durupinar, ; Visnuvinayagam, Joseph, Murugadas, Chakrabarti, & Lalitha, ), suggests handling as the major source of contamination. In this study, although, unhygienic handling of fish post‐harvest was kept to a minimum, a high prevalence of S. aureus was recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, multiplex PCR assays were developed to differentiate other methicillin‐resistant staphylococci and enterococci (Martineau et al., ; Martineau, Picard, Roy, Ouellette, & Bergeron, ; Zhang et al., ) and were used in the detection and differentiation of MRSA from fishery products in countries, namely Japan, Iran, Greece, Spain, and India (Arfatahery, Davoodabadi, & Abedimohtasab, ; Hammad, Watanabe, Fujii, & Shimamoto, ; Murugadas, Joseph, Reshmi, & Lalitha, ; Vázquez‐Sánchez, López‐Cabo, Saá‐Ibusquiza, & Rodríguez‐Herrera, ; Visnuvinayagam, Joseph, Murugadas, Chakrabarti, & Lalitha, ).…”
Section: Inconsistency In Protocols For Screening Of Mrsa In Food Matmentioning
confidence: 99%
“…Multidrug-resistant S. aureus strains are rather common in hospitals and farms but are also detected in food animals, such as pork, beef, and chicken, and in milk and fishery products in Europe, the United States, and Asia ( 6 ). The incidence of MRSA in fish and seafood was recently noted ( 7 , 8 ). Food contamination with antibiotic-resistant MRSA can be a major threat to public health, as this resistance can be transferred through resistant MRSA strains to human clinical significance ( 9 ).…”
Section: Genome Announcementmentioning
confidence: 99%